Interrelationship of Stress, Environment, and Herpes Simplex Virus Type-1 on Behçet’s Disease: Using a Mouse Model - Islam, S. M. Shamsul; Ryu, Hye-Myung; Sayeed, Hasan M.; Sohn, Seonghyang (Frontiers in Immunology, 2021)
The purpose of this study was to investigate effects of stress and environment factors on the induction of Behçet's disease (BD) using HSV-1 infected mouse model. BD is a chronic multisystemic inflammatory disease of unknown etiology. Environmental factors, immune dysfunction, and herpes simplex virus type-1 (HSV) infection might be triggers of BD. To investigate effects of environmental factors on the incidence of BD, HSV was inoculated into mice. Mice were then maintained in conventional facility or SPF facility to compare BD incidence rates. The incidence of BD was also tracked by adding stressors such as substance P (anxiety stress), 4°C (cold stress), xanthine sodium salt (oxidative stress), or 77 dB noise (noise stress). To clarify immune mechanisms involved in the difference in BD incidence caused by various stresses, dendritic cell activation markers were analyzed using flow cytometry. The combination of conventional environment, noise stress, and HSV had the highest rate of BD (38.1%) among all groups. However, HSV inoculated group in a SPF environment had the lowest incidence (2.2%). Frequencies of dendritic cell activation markers such as CD40, CD83, CD80, and CD86 were expressed differently under various stresses. Noise stress increased frequencies of CD83 cells. Noise stress also upregulated transcription factors T-bet and ROR-t. Different gut microbiota compositions were observed between SPF and conventional environment by 16S rDNA sequence analysis. Environment and stress influenced the incidence of HSV-induced BD. Microbial diversity due to environmental differences might be one explanation for regional differences in the incidence of BD.